New iterative and staggered solution schemes for incompressible fluid‐structure interaction based on Dirichlet‐Neumann coupling. (16th August 2020) - Dettmer, Wulf G.; Lovrić, Aleksander; Kadapa, Chennakesava; Perić, Djordje
Summary: In the presence of strong added mass effects, partitioned solution strategies for incompressible fluid‐structure interaction are known to lack robustness and computational efficiency. A number of strategies have been proposed to address this challenge. However, these strategies are often complicated or restricted to certain problem classes and generally require intrusive modifications of existing software. In this work, the well‐known Dirichlet‐Neumann coupling is revisited and a new combined two‐field relaxation strategy is proposed. A family of efficient staggered schemes based crucially on a force predictor is formulated alongside the classical iterative approach. Both methodologies are rigorously analyzed on the basis of a linear model problem derived from a simplified fluid‐conveying elastic tube. The investigation suggests that both the robustness and the efficiency of a partitioned Dirichlet‐Neumann coupling scheme can be improved by a relatively small nonintrusive modification of a standard implementation. The relevance of the model problem analysis for finite element‐based computational fluid‐structure interaction is demonstrated in detail for a submerged cylinder subject to an external force.